PENERAPAN SISTEM TIGA STRATA (STS) UNTUK MENGATASI MASALAH HIJAUAN MAKANAN TERNAK PADA PETANI TERNAK SAPI DI DESA PENGOTAN, KABUPATEN BANGLI - Partama, I. B. Gaga; Candrawati, D.P. M.A.; Sudiastra, I. W.; Kusumawati, N. N. Candraasih; Kayana, I. G. N. (Buletin Udayana Mengabdi, 2013)
This community service was conducted in a livestock groups of Bali cattle, one of the livestock groups is located at Pengotan village. Their members are peoples of Pengotan village, Bangli Regency. They are mostly farmers who are still having productive farm lands with very limited extensions. Nowadays, along with the care for their cattle, they usually give their cattle green forage from natural grasses. Usually, the farmers offered the cattle by rice straws from their waste of rice harvest which is plentiful enough along the year. They are only do it if they are in difficulties of getting enough fresh natural forages. Due to this condition, therefore socialization and demonstration how to place of planting high forages feedstuff (leguminoseae and nonleguminoseae) by Three Forages Stratum System (STS) for planting high quality of forages and practice of biofermentation technology for increasing the rice straw which helps to raise digestion for the livestocks. With this community service program, the expected result is the members of group have knowledge and comprehension that rice straw could be used as source of forages which could be stored within 3 to 4 months with a Microorganisms culture (EM-4) fermentation method. From this program, the participants have got appropriate knowledge to increase 90% about Three Forages Stratum System (STS) for planting high quality forages and leguminoseae threes. It is concluded that by using both the fermented rice straw and plantation of high quality of forages by Three Forages Stratum System (STS) the farmer would not be in difficulties to obtain green forages sources for their cattle.